Les besoins alimentaires de l’Afrique et la réponse du Canada : Les limites de l’aide alimentaire au développement - Charlton, Mark (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1988)
In recent years there has been an important shift in the pattern of Canadian food aid distribution towards a greater concentration on Africa. Recent projections call for increased transfers of food aid to Africa in the foreseeable future. Given the growing concern about the long-term contribution that food aid might make to increasing food sufficiency in Africa, this paper examines the concept of « developmental » food aid and its implications for Canadian food aid policy. First, the article discusses some of the problems that arise out of the provision of increased volumes of non-emergency food aid to Africa. Then, it examines the recent evolution of Canadian food aid policy with particular attention to some of the difficulties involved in implementing a strategy of providing « developmental » food aid to Africa on a long-term basis. The issues of policy dialogue, recipient selection, donor co-ordination, and food aid dependence are discussed respectively.